Effects of external radiation heat flux on combustion characteristics of pure and oil‐impregnated transformer insulating paperboard. Issue 3 (4th December 2017) - Zhang, Jiaqing; Zhang, Bosi; Fan, Minghao; Wang, Liufang; Ding, Guocheng; Tian, Yu; Chen, Qingtao
Abstract : The effects of external radiation heat flux on the combustion characteristics of pure transformer insulating paperboard (PTIP) and oil‐impregnated transformer insulating paperboard (OITIP) were investigated experimentally. The experiments were conducted with the cone calorimeter using five external radiation heat fluxes that ranged from 25 to 80 kW/m 2 . The results showed that the ignition time decreased with the external radiation heat flux, and the ignition time of PTIP was much longer than that of OITIP. Both the PTIP and OITIP are thermal thick materials, and the critical radiation heat flux of the PTIP was larger than that of the OITIP. For the PTIP, the peak of the heat release rate (HRR) and toxic gas productions had no significant difference, while those of the OITIP increased with the external radiation heat flux. The HRR peak of the PTIP was larger than that of the OITIP with the external radiation heat fluxes of 25, 35, 50, and 65 kW/m 2 . When the radiation heat flux increased to 80 kW/m 2, the HRR peak of the OITIP became higher. From the perspective of the CO production rate, the hazard of PTIP fires was more severe than that of OITIP fires under the external radiation heat fluxes of 25 and 35 kW/m 2 . The CO production rate of the PITP was lower than that of the OITP with the high external radiation heat fluxes of 50, 65 and 80 kW/m 2 . © 2017 American Institute of Chemical Engineers Process Process Saf Prog 37:362–368, 2018